2020
DOI: 10.1037/edu0000383
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of mathematical difficulties and their stability.

Abstract: Some children struggle with mathematics. Among these children, some of them may be learners with mathematical difficulties. While research has revealed multiple deficits as candidate causes for mathematical difficulties and probable subtypes, the cognitive profiles of these subtypes are not fully understood. Moreover, we have yet to discover whether children may move in or out of these subtypes over time. This study set out to identify the subtypes of mathematical difficulties as well as their stability. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(67 citation statements)
references
References 139 publications
(203 reference statements)
5
59
1
Order By: Relevance
“…In contrast to many other studies with data-driven designs (e.g., Bartelet et al, 2014;Chan and Wong, 2020), no large number of subtypes in CwD was identified in this methodically advanced study. Two subgroups of children with dyscalculia were consistently found, and this result was robust regardless of whether (a) only complete data sets or imputed data sets were used, (b) the clustering was carried out at the level of subtests (e.g., dot enumeration, magnitude comparison) or aggregated constructs (e.g., basic numerical processing) or (c) different dyscalculia assessments were used (HRT 1-4 or ZAREKI-R).…”
Section: Discussionmentioning
confidence: 70%
“…In contrast to many other studies with data-driven designs (e.g., Bartelet et al, 2014;Chan and Wong, 2020), no large number of subtypes in CwD was identified in this methodically advanced study. Two subgroups of children with dyscalculia were consistently found, and this result was robust regardless of whether (a) only complete data sets or imputed data sets were used, (b) the clustering was carried out at the level of subtests (e.g., dot enumeration, magnitude comparison) or aggregated constructs (e.g., basic numerical processing) or (c) different dyscalculia assessments were used (HRT 1-4 or ZAREKI-R).…”
Section: Discussionmentioning
confidence: 70%
“…Students with DD or arithmetic learning disabilities may experience early academic failures in schools, have lower mathematical scores, and have deficits in various numbers and number-related processing (Chan & Wong, 2020;Kucian et al, 2011). The current findings provided a new approach for Tier 1 DD instruction, suggesting that F I G U R E 3 Group comparisons among the estimated marginal means in arithmetic computation and character reading after controlling for gender, age, grade, and cognitive variables.…”
Section: Discussionmentioning
confidence: 70%
“…Students with DD or arithmetic learning disabilities may experience early academic failures in schools, have lower mathematical scores, and have deficits in various numbers and number‐related processing (Chan & Wong, 2020; Kucian et al, 2011). The current findings provided a new approach for Tier 1 DD instruction, suggesting that the abacus course could be incorporated into the general school curriculum, helping to prevent the severity of symptoms and academic deficits in students at risk of DD while they are in their early school years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations